2004
DOI: 10.1364/opex.12.004353
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative measurement of attenuation coefficients of weakly scattering media using optical coherence tomography

Abstract: Abstract. From calibrated, weakly scattering tissue phantoms (2-6 mm -1 ), we extract the attenuation coefficient with an accuracy of 0.8 mm -1 from OCT data in the clinically relevant 'fixed focus' geometry. The data are analyzed using a single scattering model and a recently developed description of the confocal point spread function (PSF). We verify the validity of the single scattering model by a quantitative comparison with a multiple scattering model, and validate the use of the PSF on the calibrated sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
263
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(269 citation statements)
references
References 19 publications
4
263
1
1
Order By: Relevance
“…The total light attenuation coefficient µ t of the tissue local volume, which is a sum of the absorption coefficient µ a and the scattering coefficient µ s , may be found by fitting the parameters of the approximating curve, calculated within the framework of the appropriate model, using the local A-scan slope of the OCT signal [18,118,[230][231][232].…”
Section: Optical Coherence Tomographymentioning
confidence: 99%
“…The total light attenuation coefficient µ t of the tissue local volume, which is a sum of the absorption coefficient µ a and the scattering coefficient µ s , may be found by fitting the parameters of the approximating curve, calculated within the framework of the appropriate model, using the local A-scan slope of the OCT signal [18,118,[230][231][232].…”
Section: Optical Coherence Tomographymentioning
confidence: 99%
“…The OCT signal attenuation coefficient is determined by a 2-parameter single exponential fit (attenuation rate and amplitude) over the region of the cuvette. It has been shown that this is a simple and valid model for the OCT signal attenuation [15]. The fitted attenuation coefficient is converted to µ s by subtracting the Intralipid concentration dependent optical absorption (0.136 mm −1 at 1300 nm wavelength for water [16] and negligible for the solid part of the Intralipid).…”
Section: Doppler Optical Coherence Tomographymentioning
confidence: 99%
“…The anisotropy factors of normal and cancer are larger than 0.8, which corresponds that tissue is generally considered to be highly forward scattering (g > 0.8) [24] . Anisotropy factors of 0.9 for tissue are very high because no correction of the OCT signal for the depth of focus of the sample arm optics and the focus position in the tissue [25,26] .…”
Section: Discussionmentioning
confidence: 99%